Educação em marketing: visões e práticas de domesticação no contexto nordestino. - Vasconcelos, Madiã Marcela Fernandes (2016)
This dissertation prioritizes the discussion about education in marketing, whereas divergent perspectives of considered and adopted on a large scale under Brazil, in this way, podering about contributions that the prospect of macromarketing can add to the current discourse, the same way that hybridization processes, domestication and/or anthropophagy can add the concepts and marketing education in courses od Bachelor’s degree in a administration, specifically in the northeast of brazil. The formulation of ideas and discussions on the reflective current panorama of marketing education in courses of Bachelor’s degree in administration is present in that document, bypassing questions covering aspects of the context and culture in education in marketing in the northeast of Brazil. Methodology qualitative procedures were adopted in great part of data. Conclusively show the opinion of teachers about aspects adopted in the classroom, in the same way that the difficulties in adapting the context, followed by recommendations that are placed, as the need to improve the scope of marketing discipline, including themes related to macromarketing and syllabus through hybridization processes, anthropophagy and/or domestication, so that the formation of Bachler’s degree in administration in based on a systemic view, which we believe fit better in current standards.